1974
DOI: 10.1346/ccmn.1974.0220109
|View full text |Cite
|
Sign up to set email alerts
|

Interlamellar and Multilayer Nitrogen Sorption by Homoionic Montmorillonites

Abstract: Abstrac~Nitrogen sorption by various homoionic montmorillonites was studied at 78~ The adsorption isotherms in the relative pressure range P/Po = 0.05-0.25 were found to be either Type I or Type II in the BET classification. The nitrogen sorption process was considered to be predominantly interlamellar when described by a Type I isotherm. With a Type II isotherm, the adsorption was assumed to be predominantly on those surfaces not in the interlamellar regions.It was concluded that only cations within a certain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1975
1975
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…Figure 4(a) for Cs + Wyoming bentonite] support the consistent agreement of the sorption process for nitrogen on these homoionic montmorillonites with the multilayer theory, as observed by Knudson and McAtee (1974), rather than with the monolayer equation. In each case, the BET plots provide good straight lines whilst the Langmuir plots show marked negative curvature, indicating that considerably more sorption is occurring than corresponds to monolayer formation.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…Figure 4(a) for Cs + Wyoming bentonite] support the consistent agreement of the sorption process for nitrogen on these homoionic montmorillonites with the multilayer theory, as observed by Knudson and McAtee (1974), rather than with the monolayer equation. In each case, the BET plots provide good straight lines whilst the Langmuir plots show marked negative curvature, indicating that considerably more sorption is occurring than corresponds to monolayer formation.…”
Section: Resultssupporting
confidence: 79%
“…Such plots are not particularly sensitive to small variations but should be adequate to judge the predominant process. Knudson and McAtee (1974) reported that for montmorillonite saturated with large dimethylammonium or Co(en) ] + ions, comparative plots of the BET and Langmuir functions indicated that significant interlamellar sorption of nitrogen did occur. In Figure 3, Vn plots for nitrogen sorption on Redhill montmorillonite saturated with hexane diammonium ions and outgassed at temperatures of 50~ 100~ and 250~ respectively, are given.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…is either quite small or partially offset by true interlamellar exchange within the clay platelets even at low exchange values. A more thorough discussion on this area of cation exchange and its surface area effects carried out on a similar cation (Co(en) 3+) has been published recently by Knudson (1974).…”
Section: Resultsmentioning
confidence: 99%
“…A corollary of this structure is that clays can expand for better pore accessibility and then contract to trap small molecules into a "sandwich" between the phyllosilicate micelles, or lamellae. Cations of medium size that would not clog the interstices between the strata can play a significant role in promoting the interlamellar sorption in dry clays (9). Also, small amounts of residual water have been shown (8) to have a profound effect on accessibility to the areas between the lamellae, forming pseudocrystals.…”
Section: Trapping Mechanismsmentioning
confidence: 99%